ผลของความเป็นกรดด่างของสารละลายไซเลนและระยะเวลารอให้สารละลายแห้งต่อการยึดติดระหว่างซี่ฟันปลอมอะคริลิคและอะคริลิคฐานฟันปลอมชนิดบ่มด้วยความร้อน - ณัฐวุฒิ คุตตะเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The aim of this study was to evaluate pH of silane solution and drying time on tensile bond strength between silane modified acrylic denture teeth and heat-cured denture base resin. MajorDentTM acrylic denture teeth were cut, polished on the ridge lap and invested in plaster mold. After dewaxing, the teeth were divided into 10 groups (N=12). The experiment consisted of 2 parts: pH and drying time. The 0.1M of γ- methacryloxypropyl trimethoxysilane solution was prepared at pH 4 and 5.5 and non-treated group were evaluated in the first part. In part II, drying time at 5 minutes, 1, 2, 3, 12, 24 hours and 14 days after silane application were examined. All samples were prepared according to the conventional denture fabrication procedures and later cut into mini-dumbbell shape with 2 X 3 mm. at the slimmest part. All specimens were incubated in 37 ℃ distilled water for 24 hours before testing. All test were performed on Universal testing machine (Instron, Model 8872) with cross head-speed of 1 mm./min. The results, analyzed by 1-way ANOVA and multiple comparison, revealed that the silane (pH = 5.5) treated group had higher tensile bond strength than the others (p<0.05). For the effect of drying time, there were no significant differences among the drying times at 5 minutes, 1, 2, 3, 12, 24 hours while the 14 days group demonstrated dramatically less strength than the others (p<0.05).